2019
DOI: 10.3847/1538-4357/aaf288
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Inertial Kinetic-Alfvén Turbulence

Abstract: Recent observational and analytical studies suggested that a new regime of kinetic turbulence may exist in plasma environments with low electron beta (Chen & Boldyrev 2017). Such a regime, termed inertial kinetic-Alfvén turbulence, is relevant for the solar corona, Earth's magnetosheath, and other astrophysical systems where the electron and ion plasma beta parameters satisfy the condition β e β i 1. In this paper we present kinetic numerical simulations that confirm existence of the iKAW regime. Specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 55 publications
1
30
0
Order By: Relevance
“…(9). nhds, like other solvers of the hot-plasma dispersion relation (Roennmark 1982;Gary 1993;Klein & Howes 2015), determines the non-trivial solutions to the wave equation,…”
Section: Plasma Waves In Linear Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…(9). nhds, like other solvers of the hot-plasma dispersion relation (Roennmark 1982;Gary 1993;Klein & Howes 2015), determines the non-trivial solutions to the wave equation,…”
Section: Plasma Waves In Linear Theorymentioning
confidence: 99%
“…achieving this ordering of scales in simulations requires sufficiently large values for m i /m e and c/v Ai . However, typical values of |Ω e |/ω e used in fully kinetic studies of the solar wind are |Ω e |/ω e ∼ 0.1 − 1 (Karimabadi et al 2013;Saito & Nariyuki 2014;Parashar et al 2015b,a;Grošelj et al 2018;Parashar & Gary 2019;Roytershteyn et al 2019), in contrast to the realistic values |Ω e |/ω e ∼ 10 −3 −10 −2 (for example, see Verscharen et al 2019, table 1). Therefore, it is important to understand and quantify the effects of artificially large values of |Ω e |/ω e on the dynamics of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the multiplicative factor in the estimate of E(k ⊥ ) in terms of E B ⊥ (k ⊥ ) is responsible for a steepening of the latter at scales smaller than d e , an effect visible in particular in the simulation with hyper-diffusivity, χ = 1, and E + (k 0 )/E − (k 0 ) = 100. A k −11/3 ⊥ spectrum, classical for balanced IKAW turbulence (Chen & Boldyrev 2017;Passot et al 2018;Roytershteyn et al 2019) is still observed for this level of imbalance. Spectra, obtained with Landau damping and electron inertia, are also displayed in this figure: for χ = 0.6 with E + (k 0 )/E − (k 0 ) = 1 or E + (k 0 )/E − (k 0 ) = 100, showing that the spectra get steeper as the imbalance increases, and for χ = 1 with E + (k 0 )/E − (k 0 ) = 100, showing that the steepening is more pronounced as χ is decreased.…”
Section: Direct Cascades In Imbalanced Turbulencementioning
confidence: 82%
“…Simulations were performed for β e = 2, τ = 1 (case I) typical of the SW at 1 AU, and β e = 0.04, τ = 10 (case II), more suitable for regions closer to the Sun (Roytershteyn et al 2019). For small β e , d e significantly exceeds the electron Larmor radius ρ e = √ 2δρ s , thus permitting electron inertia to be retained, while electron FLR corrections are neglected.…”
Section: The Modelmentioning
confidence: 99%
“…A more appropriate name for the considered equations is the “inertial kinetic‐Alfvén system” since the electron‐inertia effects play an important role in the plasma dynamics (e.g., Boldyrev & Loureiro, 2019; Roytershteyn et al, 2019). Such a system is applicable to environments with low electron plasma beta, which include the solar corona, the Earth's magnetosheath, and possibly collisionless shocks (e.g., Chandran et al, 2011; C. H. K. Chen & Boldyrev, 2017; Cranmer et al, 2009; Ghavamian et al, 2013).…”
Section: Kinetic‐alfvén Turbulence In a Low Electron‐beta Plasmamentioning
confidence: 99%